Cortisol response and psychological distress predict susceptibility to false memories for a trauma film. Issue 9 (20th October 2016) - Monds, Lauren A.; Paterson, Helen M.; Ali, Sinan; Kemp, Richard I.; Bryant, Richard A.; McGregor, Iain S.
ABSTRACT: For eyewitness testimony to be considered reliable, it is important to ensure memory remains accurate following the event. As many testimonies involve traumatic, as opposed to neutral, events, it is important to consider the role of distress in susceptibility to false memories. The aim of this study was to investigate whether cortisol response following a stressor would be associated with susceptibility to false memories. Psychological distress responses were also investigated, specifically, dissociation, intrusions, and avoidance. Participants were allocated to one of three conditions: those who viewed a neutral film ( N = 35), those who viewed a real trauma film ( N = 35), and a trauma "reappraisal" group where participants were told the film was not real ( N = 35). All received misinformation about the film in the form of a narrative. Participants provided saliva samples (to assess cortisol) and completed distress and memory questionnaires. Cortisol response was a significant predictor of the misinformation effect. Dissociation and avoidance were related to confabulations. In conclusion, following a stressor an individual may differ with regard to their psychological response to the event, and also whether they experience a cortisol increase. This may affect whether they are more distressed later on, and also whether they remember the event accurately.